LIGNIN CONTENT IN FERMENTATION OF COCOA POD (THEOBROMA COCOA) USED PLEUROTUS OSTREATUS - Engkus Ainul Yakin; Sri Sukaryani; Abbas Ummami (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2020)
The study were aimed to determine the lignin degradation in fermentation of cocoa pod with Pleurotus ostreatus. The research methods was using three treatments and four replications. T0 = fermentation of cocoa pod in 10 days, T1 = fermentation of cocoa pod in 15 days, and T2 = fermentation of cocoa pod in 20 days. The mixture was put into a container aerobically. The variables observed were dry matter (DM), crude protein (CP), crude fiber (CF), crude fat (CFt), ash and lignin content. This study was designed using the completely randomized research design with a unidirectional pattern analysis of variance (oneway ANOVA). Significant variables went through Duncan's Multiple Range Test (DMRT). The result showed that the lower lignin content was T2 = fermentation of cocoa pod in 20 days = 6.40 ± 0.12%. It could be concluded that the addition of fungus Pleurotus ostreatus on cocoa pod fermented during 20 days was the lower lignin content in fermentation of cocoa pod.